PERAN KOMPETENSI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Munawir; Muhammad Fariq Faza; Nadiah Salma Fairuzah; Muhammad Iqbaal Al Ghifari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the role of teacher competence in enhancing students’ learning motivation, which remains a key issue in education. The objective is to analyze how various dimensions of teacher competence contribute to students’ engagement in learning. This research uses a qualitative approach with a library research method, utilizing secondary data from books, journals, and relevant academic sources. Data were analyzed through content analysis by organizing and synthesizing expert perspectives. The results show that teacher competence, including pedagogical, professional, social, and personal aspects, has a significant and interconnected role in improving students’ motivation. These competencies help create an effective and supportive learning environment, encouraging students to be more active and motivated. Therefore, continuous development of teacher competence is essential to improve educational quality and learning outcomes.